Tales from the outer limits: Archaeological geophysical prospection in lowland peat environments in the British Isles. Issue 2 (21st October 2018) - Armstrong, Kayt; Cheetham, Paul; Darvill, Tim
Abstract: In order to systematically investigate the potential of conventional near surface geophysical techniques to locate waterlogged archaeological targets in peatlands, the authors applied four conventional geophysical methods – earth resistance, ground‐penetrating radar (GPR), magnetic gradiometry and frequency domain electromagnetics (FDEM) – to four lowland peat archaeological test sites in Great Britain. In this article we demonstrate that a Neolithic trackway was identified in the GPR data in Somerset, with likely 'proxy' detections of chemical changes showing up in both electrical and magnetic surveys. This was determined by a coring programme and inductively coupled plasma optical emission spectrometry (ICP‐OES) multi‐element analysis of peat samples to determine the relative concentrations of geophysically relevant chemical elements. Though no Bronze Age timbers were detected at Flag Fen, a post‐Bronze Age agricultural landscape was identified in both the GPR and gradiometer surveys. We conclude that GPR has the greatest potential for archaeological geophysical prospection in peatland environments, but that electrical and magnetic methods can usefully be employed as secondary sources of information and should not be discounted from future research. Further, this article argues that better understandings must be developed of the impacts of geochemistry on geophysical data if we are going to realistically pursue 'whole landscape' surveys.